THE JOURNEY OF MAGNUS CHASE’S CHARACTER AS MYTHICAL HERO IN THE SWORD OF SUMMER NOVEL BY RICK RIORDAN - Hera Erliani; Singgih Daru Kuncara; Indah Sari Lubis (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2019)
This research focuses on the journey of Magnus Chase’s character as the mythical hero in The Sword of Summer novel by Rick Riordan. This research has two purposes. The first is to identify the stages of Monomyth that appear in the journey of Magnus Chase’s character in The Sword of Summer novel. The second is to identify kind of Mythoi of The Sword of Summer novel. The researcher applied Joseph Campbell’s theory of Monomyth and Northrop Frye’s theory of Mythoi to answer the research questions. There are two results of this research. First, Magnus Chase’s character undergoes fifteen out of seventeen stages that proper with Campbell’s Monomyth. These fifteen stages are The Call to Adventure, Refusal of the Call, Supernatural Aid, The Crossing of the First Threshold, The Belly of the Whale, The Road of Trials, The Meeting with the Goddess, Woman as Tempress, Atonement with the Father, Apotheosis, The Ultimate Boon, Refusal of the Return, The Crossing of the Return Threshold, Master of Two World and Freedom to live. Second, the kind of Mythoi of The Sword of Summer novel is The Mythos of Summer: Romance. That is because Magnus Chase undergoes all the phases of The Mythos of Summer: Romance. These phases are the emerge of the hero, the innocent youth of the hero, the completion of an ideal, the theme of maintaining the hero’s integrity, the innocent youth of the hero and the end of the adventure. Penelitian ini berfokus pada perjalanan karakter Magnus Chase sebagai pahlawan mitos dalam novel The Sword of Summer karya Rick Riordan. Penelitian ini memiliki dua tujuan. Tujuan pertama adalah mengidentifikasi tahapan Monomyth yang muncul dalam perjalanan karakter Magnus Chase dalam novel The Sword of Summer. Tujuan kedua adalah mengidentifikasi jenis Mythoi dari novel The Sword of Summer. Peneliti menerapkan teori Monomyth yang dipopulerkan oleh Joseph Campbell dan teori Mythoi yang diperkenalkan oleh Northrop Frye untuk menjawab pertanyaan penelitian. Terdapat dua hasil dari penelitian ini. Pertama, karakter Magnus Chase mengalami lima belas dari tujuh belas tahapan yang sesuai dengan teori Monomyth dari Joseph Campbell. Lima belas tahap ini adalah The Call to Adventure, Refusal of the Call, Supernatural Aid, The Crossing of the First Threshold, The Belly of the Whale, The Road of Trials, The Meeting with the Goddess, Woman as Tempress, Atonement with the Father, Apotheosis, The Ultimate Boon, Refusal of the Return, The Crossing of the Return Threshold, Master of Two World dan Freedom to live. Kedua, jenis Mythoi dari The Sword of Summer novel adalah The Mythos of Summer: Romance. Hal tersebut terjadi karena karakter Magnus Chase mengalami semua fase dari The Mythos of Summer: Romance. Fase-fase ini adalah the emerge of the hero, the innocent youth of the hero, the completion of an ideal, the theme of maintaining the hero’s integrity, the innocent youth of the hero dan the end of the adventure.